A Phonetic Study of Vowel Epenthesis in the Dialect of Misurata: Preliminary Results (Journal of Academic Research, 2020)
A pilot phonetic study on vowel epenthesis in the dialect of Misurata was conducted. The aim of the experiment was to gain insight into the identity and behavior of the epenthetic vowel. The acoustic profile showed that the epenthetic vowel is /i/. It was also found that the epenthetic vowel occurs within CC coda clusters. In addition, the duration of the epenthetic vowel is determined by its prosodic position. For example, in single word lists the epenthetic vowel is longer than when it is embedded within a carrier phrase. This suggests that the single word behaves like a full intonational phrase where the final syllable is lengthened. The durational variation observed here is similar to that of lexical vowels when they vary in duration as a function of their prosodic position. These results suggest that CC clusters are not favorable within coda positions in this dialect. This is so despite the fact that underlying sequences do not violate the sonority sequencing principle.